Familial Adhesive Arachnoiditis Associated with Syringomyelia - Pasoglou, V. (AJNR Am J Neuroradiol, 2014)
Adhesive arachnoiditis is a rare condition, often complicated by syringomyelia. This pathologic entity is usually associated with prior spinal surgery, spinal inflammation or infection, and hemorrhage. The usual symptoms of arachnoiditis are pain, paresthesia, and weakness of the low extremities due to the nerve entrapment. A few cases have had no obvious etiology. Previous studies have reported one family with multiple cases of adhesive arachnoiditis. We report a second family of Belgian origin with multiple cases of arachnoiditis and secondary syringomyelia in the affected individuals.